Predictors Of Length Of Care For Covid-19 Patients Based On Patient Characteristics At The North Aceh Cut Mutia Hospital In 2020-2021 - Novita, Putri Tia; Girsang, Vierto Irennius; Nababan, Donal (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
According to the data released by the Indonesian Ministry of Health on November 22, 2021, Indonesia has confirmed that COVID-19 cases have reached 4,253,598 cases and 143,744 deaths, occupying the first position in the highest cases among countries in ASEAN region. One of the areas confirmed by COVID-19 is Aceh. The purpose of this study was to find out predictors of the length of care for covid-19 patients based on the characteristics of COVID-19 patients at Cut Mutia Hospital, North Aceh. This type of research is cross-sectional with secondary data. The population was all patients treated for COVID-19, both recovered and died in the COVID-19 treatment room at Cut Mutia Hospital, North Aceh, in 2020-2021, totaling 467 people with a sampling technique using proportions with a total of 200 respondents. The data used were secondary data. The data were analyzed using bivariate and multivariate approaches. The research found that there were no mean differences of length of stay between Covid-19 patients with low and higher education (p value= 0.39), with clinical symptoms and without clinical symptoms ( p value= 0.686), with comorbidities and without comorbidities (p value = 0.006), female and male ( p value= 0.038). The results obtained that the predicting variables of length of stay of the Covid-19 patients at Cut Meutia Hospital, North Aceh in 2020-2021, were gender (p value= 0.038, p< 0.05) and comorbidities (p value= 0.006, p< 0.05). It is suggested that Cut Mutia Hospital could conduct more intensive counseling and health promotion to achieve shorter length of care.